Binder, negative plate, preparation method of negative plate and lithium ion battery
By using binders containing carboxyl styrene butadiene rubber and acrylic polymer in lithium-ion batteries, the battery performance degradation and safety problems caused by expansion of silicon negative electrode materials are solved, and the low-temperature cycling performance and adhesion of the battery are improved.
Patent Information
- Application Number
- CN202411781683.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-18
AI Technical Summary
In existing lithium-ion batteries, the expansion of the silicon negative electrode material during charging leads to rapid attenuation of battery capacity and safety problems, and the poor adhesiveness of the adhesive leads to an increase in the electrode impedance, affecting battery performance.
A binder is used, and its components include carboxylic styrene butadiene rubber and acrylic polymer. By adjusting the carboxylic substitution degree, carboxylic content and glass transition temperature of carboxylic styrene rubber, a binder with high bonding properties is formed, which is used to prepare silicon negative electrode sheets and improve the bonding force between the electrode material and the current collector.
Without increasing the electrode impedance, the bonding force between the electrode material and the current collector is improved, and the low-temperature cycling and safety performance of the battery is improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a binder, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In the preparation of lithium-ion batteries, silicon negative electrode materials have higher capacitance. Unlike graphite negative electrode lithium batteries, silicon can not inhibit the growth of lithium dendrites, thus having an advantage in charging speed. The voltage platform of silicon is slightly higher than that of graphite, and it will not cause surface lithium precipitation during charging and discharging, and its safety performance is better than that of graphite negative electrode materials. Silicon negative electrode batteries will expand 3 to 4 times when charging, which will cause the battery capacity to decay rapidly, and increase the internal resistance of the battery, increase the heat generation, and may bring serious safety problems. Silicon has poor conductivity, far inferior to metal, which may affect the battery performance to a certain extent.
[0003] The binder is a polymer compound that adheres the positive and negative active materials to the current collector. Its main function is to bond the electrode active materials, conductive agents and electrode current collectors so that they have overall connectivity. However, the bonding properties of existing binders are still relatively poor, resulting in poor connectivity between them, increasing the impedance of the electrode, and thus affecting the performance of the battery. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a binder, a negative electrode sheet and a preparation method thereof, and a lithium ion battery.
[0005] In a first aspect of the present invention, a binder is provided, wherein the binder comprises carboxylated styrene-butadiene rubber and an acrylic polymer;
[0006] The carboxylated styrene-butadiene rubber meets at least one of the following conditions:
[0007] Condition A1: the carboxyl substitution degree A of the carboxyl styrene-butadiene rubber is 0.2 to 5;
[0008] Condition A2: the mass ratio B of the carboxyl group in the carboxylated styrene-butadiene rubber to the carboxylated styrene-butadiene rubber is 5% to 15%;
[0009] Condition A3: The glass transition temperature of the carboxylated styrene-butadiene rubber is C satisfying C / 100=0-0.5, wherein the unit of the glass transition temperature C is °C.
[0010] According to the binder of the embodiment of the present invention, at least the following beneficial effects are achieved: the binder contains an acrylic polymer and a specific carboxylated styrene-butadiene rubber, both the carboxylated styrene-butadiene rubber and the acrylic polymer contain carboxyl groups, and the binder can be used for the preparation of silicon negative electrodes. Through the effects of the carboxylated styrene-butadiene rubber and the acrylic polymer included in the binder, the bonding force between the electrode material and the electrode current collector can be improved with little effect on the electrode impedance, thereby improving the low-temperature cycle performance of the battery.
[0011] Specifically, the carboxyl substitution degree A is 0.2 to 5, and / or the mass ratio of carboxyl in carboxy styrene butadiene rubber to carboxy styrene butadiene rubber (i.e., the carboxyl content in carboxy styrene butadiene rubber) B is 5% to 15%, wherein the carboxyl has a high film strength and bonding performance, and when the product binder is applied to the preparation of silicon negative electrode sheets, the bonding strength between the electrode active material and the current collector can be improved, as well as the mechanical properties of the negative electrode sheet can be improved. If the carboxyl content and carboxyl substitution are too low, the bonding effect between it and other materials (such as silicon-based negative electrode materials, silicon-carbon negative electrode materials or -OH and other reactive bonding functional groups on their surfaces) and the current collector is insufficient, and thus the bonding is insufficient; if the carboxyl content and carboxyl substitution are too high, the binder is dissolved in the solvent and stirred to prepare the slurry, and the molecules are active inside, and it is very easy to react to produce bubbles, which affects the bonding performance.
[0012] In addition, below the glass transition temperature, carboxy styrene butadiene rubber generally exhibits a hard glass state, the movement of molecular segments is restricted, and the volume change is small; above the glass transition temperature, carboxy styrene butadiene rubber generally exhibits a high elastic state, the molecular segments move freely, and the volume change is significant. Therefore, the glass transition temperature directly affects the physical state and properties of carboxy styrene butadiene rubber. When carboxy styrene butadiene rubber is in a glass state, the mobility of its molecular segments is low, resulting in the overall material showing a higher hardness and lower deformation capacity. In this state, the swelling effect of carboxy styrene butadiene rubber on solvents is relatively weak, because the movement of molecular segments is restricted and it is difficult to effectively absorb solvent molecules. As the temperature rises above the glass transition temperature, the mobility of the molecular segments of carboxy styrene butadiene rubber is enhanced, allowing carboxy styrene butadiene rubber to better absorb solvents and swell. Therefore, polymers with higher glass transition temperatures have relatively lower swelling degrees at temperatures below the glass transition temperature. Furthermore, by controlling the glass transition temperature C of the carboxylated styrene-butadiene rubber within the range of C / 100=0 to 0.5, it is possible to avoid the problem that the glass transition temperature is too low (C<0°C), the binder absorbs the electrolyte and swells too much, and powdering occurs easily; and it is possible to avoid the problem that the glass transition temperature is too high (C>50°C), the wear resistance is reduced, and the low-temperature performance is reduced.
[0013] Among them, the carboxylated styrene butadiene rubber meets at least one of the above three conditions (i.e., condition A1, condition A2, and condition A3). Specifically, the carboxylated styrene butadiene rubber may meet one of the three conditions; or the carboxylated styrene butadiene rubber meets any two of the three conditions, such as meeting condition A1 and condition A2, or meeting condition A1 and condition A3, or meeting condition A2 and condition A3; or, the carboxylated styrene butadiene rubber meets all three of the above conditions.
[0014] In some embodiments of the present invention, the bonding coefficient N of the adhesive satisfies: N=A+B+(C / 100)=0.25-1.85; and / or the degree of carboxyl substitution of the acrylic polymer is greater than 0.8.
[0015] The bonding coefficient N of the binder satisfies: N=A+B+(C / 100)=0.25-1.85, in which A represents the degree of carboxyl substitution of carboxylated styrene butadiene rubber, B represents the mass ratio of carboxyl groups in carboxylated styrene butadiene rubber to carboxylated styrene butadiene rubber, and C represents the glass transition temperature of carboxylated styrene butadiene rubber, in units of °C. By controlling the bonding coefficient N of the binder to meet the above conditional formula, the bonding force between the electrode material and the electrode current collector and the low-temperature cycle performance of the battery can be further improved.
[0016] Specifically, the bonding coefficient N of the adhesive can be controlled to satisfy the above conditional formula on the basis that the carboxylated styrene-butadiene rubber meets at least one of the above three conditions (i.e., condition A1, condition A2, and condition A3); preferably, the bonding coefficient N of the adhesive can be controlled to satisfy the above conditional formula on the basis that the carboxylated styrene-butadiene rubber meets at least two of the above three conditions; further preferably, the bonding coefficient N of the adhesive can be controlled to satisfy the above conditional formula on the basis that the carboxylated styrene-butadiene rubber meets the above three conditions.
[0017] The degree of substitution of carboxyl groups in acrylic polymers is greater than 0.8, which makes it easy to form strong chemical reactions with other materials (such as silicon-based materials, silicon-carbon materials or their surfaces), enhance the mechanical properties of the electrode, and improve the cycle performance of the silicon negative electrode. For example, acrylic polymers can form a uniform coating on the surface of silicon negative electrode materials, and the surface of silicon materials generally has a SiO2 oxide layer, which is easily hydrated, so that it can form hydrogen bonds with the carboxyl groups in acrylic polymers, and further react to form ester bonds during the drying process of the electrode. This ester bond makes the acrylic polymer have a strong interaction with the surface of the silicon material, thereby improving the adhesion between the electrode material and the current collector and improving the low-temperature cycle performance of the battery.
[0018] In some embodiments of the present invention, the mass ratio of the carboxylated styrene butadiene rubber to the acrylic polymer is 5-60:2-5; further, the mass ratio of the carboxylated styrene butadiene rubber to the acrylic polymer can be controlled to be 10-50:2-4, 15-40:3-5, or 25-35:3-5.
[0019] Since acrylic polymers (such as polyacrylic acid) are generally water-soluble binders, if too much is added, it will affect the water resistance and scratch resistance of the coating when the binder is subsequently used in the preparation of silicon negative electrode sheets, making the coating neither water-resistant nor scratch-resistant; and if too little is added, the viscosity-enhancing effect cannot be effectively achieved. Therefore, by controlling the mass ratio of carboxylated styrene-butadiene rubber and acrylic polymer within the above range, the acrylic polymer can be made slightly sticky when it comes into contact with water, thereby improving the bonding effect.
[0020] In some embodiments of the present invention, the acrylic polymer is selected from at least one of polyacrylic acid (PAA) and polyacrylate.
[0021] In some embodiments of the present invention, the binder also includes carboxymethyl cellulose (CMC). The use of CMC in combination with carboxy styrene butadiene rubber and acrylic polymers can facilitate the suspension and dispersion of the components (especially carboxy styrene butadiene rubber) when the binder is used to prepare the slurry for the preparation of the pole piece, thereby preventing sedimentation; and can also help improve the structural toughness and prevent the pole piece from swelling in the electrolyte.
[0022] In some embodiments of the present invention, the carboxyl substitution degree of the carboxyl cellulose is greater than 0.8. The carboxyl substitution degree of the carboxyl cellulose greater than 0.8 has a function similar to that of an acrylic polymer with a carboxyl substitution degree greater than 0.8, and the acrylic polymer forms a more uniform coating on the surface of the silicon negative electrode material. The above carboxyl methyl cellulose and acrylic polymer combination are compounded with the above carboxylated styrene-butadiene rubber, and the three interact with each other, which can significantly improve the adhesion between the electrode material and the current collector and improve the low-temperature cycle performance of the battery.
[0023] In some embodiments of the present invention, the mass ratio of the carboxylated styrene butadiene rubber, the acrylic polymer and the carboxymethyl cellulose is 5 to 60: 2 to 5: 1 to 10. Further, the mass ratio of the carboxylated styrene butadiene rubber, the acrylic polymer and the carboxymethyl cellulose can be controlled to be 10 to 50: 2 to 4: 1 to 8, 15 to 40: 3 to 5: 2 to 6, or 25 to 35: 3 to 5: 3 to 6.
[0024] A second aspect of the present invention provides a negative electrode sheet comprising any one of the aforementioned binders.
[0025] In some embodiments of the present invention, the negative electrode sheet comprises:
[0026] Anode current collector;
[0027] A conductive adhesive layer, the conductive adhesive layer is disposed on at least one side of the negative electrode current collector; the raw material components of the conductive adhesive layer include a conductive agent and the binder;
[0028] A silicon negative electrode material layer is disposed on a surface of the conductive adhesion layer that is away from the negative electrode current collector.
[0029] The negative electrode sheet is a silicon negative electrode sheet, in which a conductive adhesion layer is arranged between the silicon negative electrode material layer and the negative electrode current collector. The surface of the silicon negative electrode material layer generally contains -OH and / or SiO2 oxide layer, and the conductive adhesion layer contains acrylic polymer and specific carboxyl styrene-butadiene rubber, both of which contain carboxyl groups and can be tightly combined with the surface of the silicon negative electrode through chemical bonding, thereby improving the adhesion between the electrode material and the current collector. When the negative electrode sheet is further used in battery preparation, the low-temperature cycle performance of the battery can be improved.
[0030] In some embodiments of the present invention, the raw material components of the conductive adhesive layer also include a defoamer. Polar functional groups with more hydroxyl groups are prone to produce a large amount of foam during stirring, and the presence of foam will hinder the uniform distribution of various components in the battery slurry, thereby affecting the charge and discharge performance of the battery. The use of a defoamer can eliminate the foam and make the distribution of various components in the slurry more uniform, thereby improving the battery performance.
[0031] In some embodiments of the present invention, the mass ratio of the binder, the conductive agent and the defoamer in the conductive adhesive layer can be controlled to be 8-75:30-50:0.001-0.01. If the binder contains carboxylated styrene butadiene rubber and acrylic polymer, the mass ratio of carboxylated styrene butadiene rubber, acrylic polymer, conductive agent and defoamer in the conductive adhesive layer can be controlled to be 5-60:2-5:30-50:0.001-0.01; if the binder contains carboxylated styrene butadiene rubber, acrylic polymer and carboxymethyl cellulose, the mass ratio of carboxylated styrene butadiene rubber, acrylic polymer, carboxymethyl cellulose, conductive agent and defoamer in the conductive adhesive layer can be controlled to be 5-60:2-5:1-10:30-50:0.001-0.01.
[0032] In some embodiments of the present invention, the conductive adhesion layer is disposed on both side surfaces of the negative electrode current collector.
[0033] In some embodiments of the present invention, the conductive agent is selected from at least one of conductive carbon black, graphene, superconducting carbon black, graphite, expanded graphite, carbon nanotubes, and activated carbon.
[0034] In some embodiments of the present invention, the negative electrode current collector is selected from copper foil; and / or the negative electrode current collector has a thickness of 5 μm to 15 μm.
[0035] In some embodiments of the present invention, the components of the silicon negative electrode material layer include a negative electrode active material, and the negative electrode active material is selected from silicon-based negative electrode materials or silicon-carbon negative electrode materials.
[0036] The compaction density of silicon negative electrode is generally selected according to the characteristics of the main material (negative electrode active material). Different negative electrode active materials will have different compaction densities. Under different coating weights, the higher the compaction density, the smaller the thickness, the smaller the design thickness of the battery cell, the smaller the volume, and the greater the energy density of the battery cell. In some embodiments of the present invention, the thickness H of the negative electrode sheet is 60μm to 100μm, and the bonding coefficient N>0.4%H. If the bonding coefficient is too low, the bonding strength with the silicon negative electrode material layer is not high, the compaction density is small, and the energy density of the battery cell is low. Therefore, by controlling the above parameters, the bonding strength of the conductive adhesion layer to the negative electrode current collector and the silicon negative electrode material layer can be improved, and the compaction density can be increased, thereby increasing the energy density of the battery cell.
[0037] In some embodiments of the present invention, the negative electrode sheet can also be designed to include a negative electrode current collector and a silicon negative electrode material layer; the silicon negative electrode material layer is arranged on at least one side surface of the negative electrode current collector, and the components of the silicon negative electrode material layer include a binder, and the binder is any of the aforementioned binders.
[0038] In some embodiments of the present invention, the silicon negative electrode material layer further includes a negative electrode active material and a conductive agent; the negative electrode active material is selected from silicon-based negative electrode materials or silicon-carbon negative electrode materials.
[0039] In a third aspect of the present invention, a method for preparing any of the above-mentioned negative electrode sheets is provided, comprising the following steps:
[0040] S1, mixing raw material components including a conductive agent and a binder with a solvent to prepare a mixed slurry, and coating the mixed slurry on at least one side of the negative electrode current collector to form a conductive adhesion layer;
[0041] S2. Prepare a silicon negative electrode material layer on the surface of the conductive adhesion layer away from the negative electrode current collector.
[0042] In some embodiments of the present invention, in step S1, the preparation of the mixed slurry satisfies at least one of the following conditions:
[0043] Condition B1: The mass content of the binder in the mixed slurry is 5% to 40%;
[0044] Condition B2: The mass proportion of the conductive agent in the mixed slurry is 20% to 60%;
[0045] Condition B3: The raw material components further include a defoamer, and the mass content of the defoamer in the mixed slurry is 0.01% to 0.3%.
[0046] Among them, controlling the mass content of the binder in the mixed slurry to 5% to 40% can improve the bonding strength while avoiding excessive binder content, which will lead to an increase in the resistance of the negative electrode sheet, and then increase the resistance of the battery cell, and reduce the low-temperature cycle performance. Specifically, if the binder content is too high (more than 40%), the resistance of the negative electrode sheet will increase, and the ratio of the resistance value of the negative electrode current collector to the resistance value after the conductive adhesion layer is set on both sides of the current collector is less than 1%, the overall battery cell resistance will increase, and the low-temperature cycle performance will deteriorate.
[0047] The mass content of the defoamer in the mixed slurry is 0.01% to 0.3%, which can ensure effective defoaming while ensuring the wetting performance of the slurry on the negative electrode current collector during the coating process, and improve the uniformity and adhesion of the conductive adhesion layer. If the defoamer content is too small (less than 0.01%), it is not enough to eliminate the foam in the mixed slurry; if the defoamer content is too high (more than 0.3%), it is easy to reduce the surface energy of the mixed slurry, and it cannot well infiltrate the negative electrode current collector, and the coating preparation process is easy to cause pinhole leakage and other phenomena.
[0048] In some embodiments of the present invention, the viscosity of the mixed slurry is 20 mPa·s to 1000 mPa·s; and / or the solvent is water.
[0049] In some embodiments of the present invention, in step S1, the mixed slurry is coated on at least one side of the negative electrode current collector, and then dried to form a conductive adhesion layer. The drying temperature can be controlled at 60° C. to 70° C. In addition, the mixed slurry can be coated on the surface of the negative electrode current collector by gravure roll printing.
[0050] In a fourth aspect of the present invention, the aforementioned lithium-ion battery is provided, comprising any of the aforementioned negative electrode sheets or a negative electrode sheet prepared by any of the aforementioned methods for preparing a negative electrode sheet.
[0051] In some embodiments of the present invention, the lithium-ion battery further includes a positive electrode sheet and a separator, and the separator is sandwiched between the positive electrode sheet and the negative electrode sheet. DETAILED DESCRIPTION
[0052] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0053] Example A1
[0054] A binder is composed of a mixture of carboxylated styrene butadiene rubber, polyacrylic acid (PAA) and carboxymethyl cellulose (CMC) in a mass ratio of 30:3:3. The carboxylated styrene butadiene rubber is purchased from Shanghai Daoying Co., Ltd. with a product model of GD102, the carboxyl substitution degree A of the carboxylated styrene butadiene rubber is 0.68, the carboxyl content B in the carboxylated styrene butadiene rubber is 10%, the glass transition temperature C is 6.28°C, and the bonding coefficient N satisfies: N=A+B+(C / 100)=0.8428; the polyacrylic acid is purchased from Jiangsu Arkema (China) Investment Co., Ltd. with a product model of XP4414; and the carboxymethyl cellulose is purchased from Finnish Novieat Company with a product model of Cellcosan2000.
[0055] Examples A2 to A15 and Comparative Examples A1 to A7
[0056] Examples A2 to A15 and Comparative Examples A1 to A7 respectively prepared a binder, and specifically, the binder was prepared by mixing materials according to the component configuration shown in Table 1.
[0057] Table 1 Component configuration of binder
[0058]
[0059] Example B1
[0060] A negative electrode sheet includes a negative electrode current collector, a conductive adhesive layer and a silicon negative electrode material layer, wherein the conductive adhesive layer is arranged on both sides of the negative electrode current collector, and the silicon negative electrode material layer is arranged on the conductive adhesive layer on one side of the surface away from the negative electrode current collector. The raw material components of the conductive adhesive layer include a binder, a conductive agent and a defoamer in a mass ratio of 36:50:0.01, the binder adopts the binder of Example A1 (containing carboxylated styrene-butadiene rubber, polyacrylic acid and carboxymethyl cellulose in a mass ratio of 30:3:3), the conductive agent is carbon black, and the defoamer is a non-ionic modified polyether substance, which is purchased from Jiangsu Yite New Materials Co., Ltd., and the product model is YT-R001.
[0061] The preparation method comprises the following steps:
[0062] S1. Take a copper foil with a thickness of 6 μm as the negative electrode current collector.
[0063] S2. Referring to Table 2, the binder, conductive agent, and defoaming agent prepared in Example A1 were mixed with deionized water in a mass ratio of 36:50:0.01:13.99, and stirred evenly to prepare a mixed slurry with a viscosity of 528 mPa·s.
[0064] S3. Use gravure roller coating to transfer the mixed slurry obtained in step S2 to the surfaces of both sides of the negative electrode current collector copper foil. The coating thickness is 1 μm. Visually observe the foil leakage after coating; then transfer the coated copper foil to a 60-70°C oven for drying to form a conductive adhesion layer on the surface of the negative electrode current collector.
[0065] S4. Take silicon active material (silicon particles), conductive carbon black, carboxymethyl cellulose (CMC) and styrene butadiene emulsion in a mass ratio of 95:1:2.7:1.3, dissolve the carboxymethyl cellulose (CMC) completely under vacuum to obtain a water-soluble polymer solution; add conductive carbon black and carbon nanotubes to the water-soluble polymer solution, and stir quickly until the fineness is less than 5 μm; then add silicon active material, and stir quickly until the fineness is less than 30 μm; reduce the speed, add styrene butadiene emulsion, and stir slowly under vacuum to obtain negative electrode slurry;
[0066] S5. Apply the negative electrode slurry obtained in step S4 onto the conductive adhesion layer formed on the surface of the negative electrode current collector, dry it, form a silicon negative electrode material layer on the conductive adhesion layer, and obtain a negative electrode sheet.
[0067] Examples B2 to B16 and Comparative Examples B1 to B9
[0068] Examples B2 to B16 and Comparative Examples B1 to B8 respectively prepared a negative electrode sheet. The differences between each example and comparative example and Example B1 mainly lie in: the selection and dosage of the binder in the mixed slurry preparation process in step S2, and the amount of defoaming agent added. Specifically, Examples B2 to B16 and Comparative Examples B1 to B8 respectively prepared mixed slurries according to the raw material component configuration in Table 2, and other operations were the same as Example B1.
[0069] Comparative Example B9 prepared a negative electrode sheet, which differs from Example B1 in that: Step S2 and Step S3 in Example B1 are eliminated in this comparative example, that is, the preparation of the conductive adhesion layer between the silicon negative electrode material layer and the negative electrode current collector is eliminated, and other operations are the same as Example B1. The final negative electrode sheet includes a negative electrode current collector and a silicon negative electrode material layer disposed on both sides of the negative electrode current collector.
[0070] Example C1
[0071] A lithium ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is sandwiched between the positive electrode sheet and the negative electrode sheet. The negative electrode sheet of this embodiment adopts the negative electrode sheet prepared in Example B1.
[0072] The preparation method comprises the following steps:
[0073] S1. Take polyvinylidene fluoride, conductive carbon, and lithium iron phosphate in a mass ratio of 1:1:1, mix them with solvent N-methylpyrrolidone (NMP) and stir them evenly to prepare a positive electrode slurry with a viscosity of 5500 Pa.s; apply it on the positive electrode collector aluminum foil, and then dry it at 100°C, cold press it to trim the edges and cut it into strips, and weld it to make a positive electrode sheet.
[0074] S2, combining a mixture of ethylene carbonate, propylene carbonate and diethyl carbonate in a volume ratio of 1:1:1 with lithium hexafluorophosphate (LiPF6, concentration of 1 mol / L) to prepare an electrolyte;
[0075] S3, stacking and winding the positive electrode sheet, the separator and the negative electrode sheet into a battery cell, injecting the electrolyte, and sealing, standing, forming, aging and finally sealing the lithium-ion battery.
[0076] Examples C2 to C16 and Comparative Examples C1 to C9
[0077] Examples C2 to C16 and Comparative Examples C1 to C9 respectively prepare a lithium ion battery, and the difference between each example and the comparative example and Example C1 is that the negative electrode sheets used are different, and the other operations are the same as Example C1. Examples C2 to C16 and Comparative Examples C1 to C9 respectively correspond to the negative electrode sheets of Examples B2 to B16 and Comparative Examples B1 to B9, and refer to Table 2 for details.
[0078] Performance Testing
[0079] (I) Adhesion performance test
[0080] First, the negative electrode sheets prepared in Examples B1 to B16 and Comparative Examples B1 to B9 were subjected to dry adhesion and wet adhesion tests; and then the simulated battery cells were rolled and subjected to dry adhesion and wet adhesion tests.
[0081] Among them, the dry adhesion test is carried out at room temperature, and the specific operation is as follows: cut the sample negative electrode sheet into strips of specified size, use a universal tensile testing machine to peel off the strip sample, and record the force value data during separation.
[0082] The specific operation method of the wet adhesion test is as follows: place the negative electrode sheet in the configured electrolyte, let it stand and soak at room temperature for 24 hours, then place the negative electrode sheet after standing in the configured electrolyte, let it stand and soak at 45°C for 24 hours; then cut the sample negative electrode sheet into strips of specified size, peel off the strip sample with a universal tensile testing machine, and record the data during separation.
[0083] The above method was used to roll the negative electrode sheets and simulated cells of each embodiment and comparative example and then conduct dry adhesion and wet adhesion tests. The results are shown in Table 2.
[0084] (II) Cycle performance test
[0085] At -20℃, the lithium-ion battery is charged to 3.0V, 3.2V and 3.4V at 1C constant current, then charged to 3.0V, 3.2V and 3.4V at constant voltage until the current is less than 0.05C, and then the lithium-ion battery is discharged to 3.0V, 3.2V and 3.4V at 1C constant current. This is a charge and discharge process. Repeat the charge and discharge in this way, and calculate the capacity retention rate of the lithium-ion battery after 800 cycles.
[0086] The lithium ion batteries prepared in Examples C1 to C16 and Comparative Examples C1 to C9 were subjected to cycle performance tests according to the above method. The results are shown in Table 2.
[0087] Table 2
[0088]
[0089] As shown in Table 2 above, by comparing the test results of the negative electrode sheets of Examples B1 to B4 and the test results of the lithium ion batteries of Examples C1 to C4, it can be seen that the carboxyl content of the carboxyl styrene butadiene rubber in the binder and the bonding coefficient N of the binder will affect the bonding of the conductive adhesion layer in the negative electrode sheet and the cycle performance of the lithium ion battery. If the carboxyl content in the carboxyl styrene butadiene rubber is too low or too high, the bonding performance and the capacity retention rate of the battery will be reduced, and the low temperature performance will be deteriorated; if the bonding coefficient is too low or too high, the bonding performance and the capacity retention rate will also be reduced. Among them, if the carboxyl content is too high, too much carboxyl will produce a large swelling, reducing the bonding performance; and, too much carboxyl content causes the corresponding bonding coefficient to be too high, resulting in a large expansion coefficient, thereby reducing the bonding. In addition, the carboxyl content in the carboxyl styrene butadiene rubber can be controlled to 5% to 15%, and the bonding coefficient N of the binder can be controlled to 0.25 to 1.85.
[0090] By comparing the performance test results of the negative electrode sheets of Example B1 and Example B5-B7, and the test results of the lithium ion batteries of Example C1 and Example C5-C7, it can be seen that the glass transition temperature of the carboxyl styrene butadiene rubber in the binder will also affect the adhesion of the conductive adhesion layer in the negative electrode sheet and the cycle performance of the lithium ion battery, and its glass transition temperature is too high or too low, which will reduce the adhesion performance and the low-temperature capacity retention rate of the battery, and thus the glass transition temperature C of the carboxyl styrene butadiene rubber can be controlled to satisfy C / 100=0-0.5.
[0091] By comparing the test results of the negative electrode sheets of Example B1 and Example B8, and the test results of the lithium ion batteries of Example C1 and Example C8, it can be seen that the carboxyl substitution degree of carboxyl styrene butadiene rubber in the binder affects the adhesion of the conductive adhesion layer in the negative electrode sheet and the cycle performance of the lithium ion battery. If the carboxyl substitution degree is too high, the adhesion performance and the low-temperature capacity retention rate of the battery will be reduced; if the carboxyl substitution degree is too low, the adhesion performance and the low-temperature capacity retention rate of the battery will also be reduced. Therefore, the carboxyl substitution degree of carboxyl styrene butadiene rubber can be controlled within 0.2 to 1.5.
[0092] By comparing the test results of the negative electrode sheets of Example B1 and Example B9-B10, and the test results of the lithium ion batteries of Example C1 and Example C9-C10, it can be seen that the degree of carboxyl substitution of polyacrylic acid and carboxymethyl cellulose affects the adhesion of the conductive adhesion layer in the negative electrode sheet and the cycle performance of the lithium ion battery. Too low carboxyl substitution will reduce the adhesion performance and the low-temperature capacity retention rate of the battery, and thus the degree of carboxyl substitution of polyacrylic acid and carboxymethyl cellulose is controlled to be greater than 0.8.
[0093] Comparing the test results of the negative electrode sheets of Example B1, Example B11 and Comparative Examples B1 to B5, and the test results of the lithium ion batteries of Example C1, Example C11 and Comparative Examples C1 to C5, it can be seen that the composite of carboxylated styrene butadiene rubber, polyacrylic acid and carboxymethyl cellulose interacts with each other, has excellent bonding performance, and the battery has a high low-temperature cycle capacity retention rate; the lack of any one of them will significantly reduce the product performance, especially carboxylated styrene butadiene rubber, which has a significant impact on the performance of the binder and its application product negative electrode sheet and lithium ion battery. The lack of this component will significantly reduce the bonding performance, cause foil leakage, and significantly reduce the low-temperature cycle capacity retention rate of the lithium ion battery. In addition, compared with carboxymethyl cellulose, polyacrylic acid has a greater impact on product performance, and thus the binder in the negative electrode sheet of Example B11 does not add carboxymethyl cellulose, and also has good product performance. The comparative example B6 negative electrode sheet uses the comparative example A6 binder. Since the carboxyl content in the carboxyl styrene butadiene rubber is less than 5%, the carboxyl substitution degree is less than 0.2, and the glass transition temperature of the carboxyl styrene butadiene rubber is also lower than 0°C, foil leakage occurs, and foil leakage will cause uneven expansion rate, which may easily lead to lithium ion precipitation and even safety problems.
[0094] Comparing the test results of the negative electrode sheets of Example B1, Example B12 and Comparative Example B8, and the test results of the lithium ion batteries of Example C1, Example C12 and Comparative Example C8, it can be seen that the addition of the defoamer in the mixed slurry used to prepare the conductive adhesive layer has a great influence on the adhesion of the conductive adhesive layer and the low-temperature cyclability of the product lithium ion battery. The addition of the defoamer can eliminate the foam of the mixed slurry, but if the amount of the defoamer added is too large, it will significantly reduce the adhesion performance of the product, the negative electrode sheet will show leakage, and the low-temperature cycle capacity retention rate of the lithium ion battery will be significantly reduced. The defoamer itself has the characteristics of a surfactant, which can reduce the surface tension of the liquid and destroy the stability of the bubbles. However, when the amount of the defoamer added is too much, too much surfactant will gather on the surface of the slurry, which will cause the emulsification, stratification or gelation of the slurry, greatly reducing the stability of the slurry, and even greater than the impact of not adding the defoamer, leakage will occur, the performance of the battery will decrease, and the life of the battery will be shortened. Because too much defoaming agent will cause changes in the electrolyte concentration in the battery, thus affecting the battery performance; the defoaming agent will affect the chemical reaction of the battery and shorten the battery life.
[0095] In addition, by comparing the test results of the negative electrode sheets of Examples B1 to B16 and the negative electrode sheets of Comparative Examples B7 and B9, as well as the test results of the lithium ion batteries of Examples C1 to C16 and Comparative Examples C7 and C9, it can be seen that by providing a conductive adhesion layer between the silicon negative electrode material layer of the negative electrode sheet and the negative electrode current collector, and the conductive adhesion layer adopts the binder of Examples A1 to A15, wherein a specific carboxylated styrene-butadiene rubber and polyacrylic acid (especially polyacrylic acid with a carboxyl substitution degree greater than 0.8) are compounded, or carboxymethyl cellulose (especially carboxymethyl cellulose with a carboxyl substitution degree greater than 0.8) is further compounded on this basis, the adhesion between the electrode material and the electrode current collector can be improved with little effect on the electrode impedance, thereby improving the low-temperature cycle capacity retention rate of the battery. However, by comparing the test results of the negative electrode sheets of Example B1 and Comparative Example B7, as well as the test results of the lithium-ion batteries of Example C1 and Comparative Example C7, it can be seen that if the content of the binder in the conductive adhesion layer is too high, the resistance of the negative electrode sheet will increase, and the low-temperature cycle performance of the battery will deteriorate. For this reason, the mass content of the binder in the mixed slurry can be controlled at 5% to 40%.
[0096] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A binder, characterized in that: The components of the binder include carboxylated styrene-butadiene rubber and acrylic polymer; The carboxylated styrene-butadiene rubber meets at least one of the following conditions: Condition A1: the carboxyl substitution degree A of the carboxyl styrene-butadiene rubber is 0.2 to 5; Condition A2: the mass ratio B of the carboxyl group in the carboxylated styrene-butadiene rubber to the carboxylated styrene-butadiene rubber is 5% to 15%; Condition A3: The glass transition temperature of the carboxylated styrene-butadiene rubber is C satisfying C / 100=0-0.5, wherein the unit of the glass transition temperature C is °C.
2. The adhesive according to claim 1, characterized in that The bonding coefficient N of the adhesive satisfies: N=A+B+(C / 100)=0.25-1.85; and / or the degree of carboxyl substitution of the acrylic polymer is greater than 0.
8.
3. The adhesive according to claim 1, characterized in that The mass ratio of the carboxylated styrene-butadiene rubber to the acrylic polymer is 5-60:2-5; and / or the acrylic polymer is selected from at least one of polyacrylic acid and polyacrylate.
4. The adhesive according to any one of claims 1 to 3, characterized in that The binder also includes carboxymethyl cellulose.
5. The adhesive according to claim 4, characterized in that The carboxyl substitution degree of the carboxymethyl cellulose is greater than 0.8; and / or the mass ratio of the carboxylated styrene-butadiene rubber, the acrylic polymer and the carboxymethyl cellulose is 5-60:2-5:1-10.
6. A negative electrode sheet, characterized in that: The invention comprises the binder according to any one of claims 1 to 5.
7. The negative electrode sheet according to claim 6, characterized in that: The negative electrode sheet comprises: Anode current collector; A conductive adhesive layer, the conductive adhesive layer is disposed on at least one side of the negative electrode current collector; the raw material components of the conductive adhesive layer include a conductive agent and the binder; A silicon negative electrode material layer is disposed on a surface of the conductive adhesion layer that is away from the negative electrode current collector.
8. The negative electrode sheet according to claim 7, characterized in that: The raw material components of the conductive adhesive layer also include a defoaming agent; And / or, the components of the silicon negative electrode material layer include negative electrode active materials, and the negative electrode active materials are selected from silicon-based negative electrode materials or silicon-carbon negative electrode materials.
9. The method for preparing a negative electrode sheet according to any one of claims 6 to 8, characterized in that: The following steps are involved: S1, preparing a mixed slurry by mixing raw material components including a conductive agent and a binder with a solvent, and coating the mixed slurry on at least one side surface of the negative electrode current collector to form a conductive adhesion layer; S2. Prepare a silicon negative electrode material layer on the surface of the conductive adhesion layer facing away from the negative electrode current collector.
10. The method for preparing a negative electrode sheet according to claim 9, characterized in that: In step S1, the preparation of the mixed slurry satisfies at least one of the following conditions: Condition B1: The mass content of the binder in the mixed slurry is 5% to 40%; Condition B2: The mass proportion of the conductive agent in the mixed slurry is 20% to 60%; Condition B3: The raw material components further include a defoamer, and the mass content of the defoamer in the mixed slurry is 0.01% to 0.3%.
11. A lithium ion battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 6 to 8 or a negative electrode sheet prepared by the method for preparing the negative electrode sheet according to any one of claims 9 to 10.